Study on Ferromagnetism in Mn-Implanted Ge/Si Nanostructure Material - Yoon, Im Taek (New Frontiers in Physical Science Research Vol. 6, 2023)
It is expected that the Moore's law progression of conventional CMOS technology will end in less than two decades and there is a worldwide search for new devices that can either extend Moore's law or provide a totally new pathway for information processing. Integration of electron charge and spin degrees of freedom represents the new challenging field of the so-called spintronics or spin-polarized electronics. Mn-based diluted magnetic semiconductors have hole-mediated ferromagnetic properties, which makes it possible to control the magnetism by electrically modulating the carriers in the semiconductor. Raising Curie temperature above room temperature might be achievable with additional carrier doping, as observed in highly doped II-VI and III-V diluted ferromagnetic semiconductors, and/or other magnetic ions, such as Cr, Co, Fe, and Ni. It is plausible that magnetically doped Ge and Si, and related materials, can open the way to room-temperature spintronic devices. This research is based upon the manipulation of magnetism in Ge quantum dots for developing spintronic devices. The material we use to create a spintronic device is the diluted magnetic semiconductor GeMn quantum dots. In order to create a spin exchange switch, the initial step is to introduce the diluted ferromagnetism into Ge by incorporating Mn into the Ge lattice. We choose ion implantation because it is a well-established and widely used technology in the semiconductor industry. The controllability of ferromagnetism in this material system is a major step towards the Ge-based spintronic devices. Multi-stacked Ge quantum dots (QDs) with Si spacers of different thicknesses have been grown on (100) Si substrates by rapid thermal chemical vapor deposition followed by Mn ion implantation and post-annealing. The presence of ferromagnetic structure was confirmed in the insulating (Si0.45Ge0.55)Mn0.03 diluted magnetic quantum dots (DMQD) and semiconducting (Si 0.45Ge0.55)Mn0.05 DMQD. With a Curie temperature of TC = 350 and 160 K, the DMQD materials were discovered to be homogeneous, display p-type conductivity, and had ferromagnetic ordering. According to x-ray diffraction (XRD) measurements, Mn5Ge3 has phased out of the MnGe nanostructure. The temperature-dependent electrical resistivity in semiconducting DMQD material indicates that manganese introduces two acceptor levels in germanium, at 0.14 eV from the valence band and 0.41 eV from the conduction band implying Mn substituting Ge. As a result, it is believed that the ferromagnetic exchange coupling of DMQD material with TC = 160 K is hole mediated due to the creation of bound magnetic polarons and that the ferromagnetism in a sample with TC > 300 K is caused by the Mn5Ge3 phase.